BACTERIAL QUALITY AND DEPURATION OF THE GREEN MUSSEL PERNA VIRIDIS FROM NATURAL BEDS - MALARVANNAN, G.; EDWARD, J. K. PATTERSON (Journal of Indian Fisheries Association, 2015)
Green mussel (Perna viridis) and sea water from their natural beds on the coastal areas of Porto Novo were studied between April and August 1996 for their bacterial quality. Water samples from the beds were also analysed for their physico-chemical parameters. The total bacterial count of nn.1ssels from natural beds as well as bed waters ranged 103 organisms per gramme of n1ussel meat suspension and per Inillilitre of sea water. The faecal coliforms were found to be within the permissible limits. Pathogenic bacteria such as Sabnonella spp., Streptococcus spp. and Staphylococcus spp. were absent. The variations in pH, temperature, salinity and dissolved oxygen of the seawater samples were insignificant. The mussels were subjected to depuration by different methods among which chlorination was found to be most effective. Keywords : Mussel, Perna viridis, bacterial quality, depuration